The characteristics of Roman Private Law Sources - K. S. Naumenko (Bulletin of Kharkiv National University of Internal Affairs)
The article establishes that the sources of Roman Private Law are the ways of consolidation and external expression of legal norms which, in their entirety, were aimed at regulating private legal relations.